Transcoding abilities in typical and atypical mathematics achievers: The role of working memory and procedural and lexical competencies. - Moura, Ricardo; Wood, Guilherme; Pinheiro-Chagas, Pedro; Lonnemann, Jan; Krinzinger, Helga; Willmes, Klaus; Haase, Vitor Geraldi (Journal of Experimental Child Psychology, 2013)
Highlights: [•] We studied number transcoding in children with and without math difficulties. [•] Younger children with math difficulties struggled with numerical lexicon and syntax. [•] Older children with math difficulties struggled with numerical syntax only. [•] Working memory did not fully account for the group differences. [•] Children with math difficulties showed a delay in the learning of number transcoding.